The influence of Brand Awareness on Purchase Decision Mediated by Purchase Interest on Cosmetic Products Online in Medan City - Tirtayasa, Satria; Khair, Hazmanan; Tusakdiah, Halimah (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study aims to analyze and determine the effect of Brand Awareness and Online Customer Reviews on the purchasing decision of Maybelline lipstick products in online e-commerce among students in Medan. The study uses an associative approach with a sample of 386 students who use Maybelline lipstick. Data was collected through questionnaires, and the data was analyzed using quantitative analysis with Smart PLS (Partial Least Squares) for hypothesis testing and model evaluation. The findings show that Brand Awareness has a significant influence on the purchasing decision of Maybelline lipstick products in e-commerce. Online Customer Reviews also significantly affect the purchasing decision of Maybelline lipstick in e-commerce. Furthermore, Brand Awareness significantly influences the purchase interest in Maybelline lipstick, while Online Customer Reviews similarly affect purchase interest. Purchase interest, in turn, significantly influences the purchasing decision of Maybelline lipstick in e-commerce. The results also show that Brand Awareness affects purchasing decisions through purchase interest, as does Online Customer Reviews.